Older Adults and the COVID-19 Pandemic, What About the Oldest Old? The PACOVID Population-Based Survey - Hernández-Ruiz, Virgilio; Meillon, Céline; Avila-Funes, José-Alberto; Bergua, Valérie; Dartigues, Jean-François; Koleck, Michèle; Letenneur, Luc; Ouvrard, Camille; Pérès, Karine; Rascle, Nicole; Tabue-Teguo, Maturin; Amieva, Hélène (Frontiers in Psychiatry, 2021)
Introduction: The literature draws a mitigated picture of the psychosocial effects of the lockdown in older adults. However, the studies conducted so far are mainly based on web surveys which may involve selection bias. The PACOVID survey relies on a population-based design and addresses the attitudes, psychological and social experiences of the oldest old regarding the pandemic and lockdown and their impact. Material and Methods: Cross-sectional phone survey involving 677 participantspersons. Baseline report on attitudes, psychological and social experiences of the oldest old, regarding the pandemic and lockdown measures. Results: The mean age was 878.538 (SD 5.197). About 46% were living alone during the lockdown. Concerning difficulties, “none” was the most frequent answer (35.6%). For questions addressing how often they had felt sad, depressed, or lonely (CESD-scale), the most frequent answers were “never/very rarely” (58.7%, 76.6%, 60.8%) and 27.1% had anxious symptomatology (STAI scale). Most (92.9%) felt socially supported. Engaging in leisure activities was the most frequent coping strategy, and for numerous participants the lockdown did not represent much of a change in terms of daily routine. A very good knowledge and awareness of COVID-19 and the safety measures was observed. Comparisons with measures collected before the pandemic showed low changes in subjective health and the CES-D questions. Discussion: With a methodological design limiting selection bias, our results claim for a weakened psychosocial impact even though the participants are concerned and aware of the pandemic issues. These results highlight the resources and resilience abilities of older persons including in advancing age.